Plant species composition and diversity in traditional agroforestry landscapes on Siberut Island, West Sumatra, Indonesia - GUSMARDI INDRA; ERIZAL MUKHTAR; SYAMSUARDI SYAMSUARDI; CHAIRUL CHAIRUL; MANSYURDIN MANSYURDIN (Society for Indonesian Biodiversity, 2024)
Abstract. Indra G, Mukhtar E, Syamsuardi, Chairul, Mansyurdin. 2024. Plant species composition and diversity in traditional agroforestry landscapes on Siberut Island, West Sumatra, Indonesia. Biodiversitas 25: 1286-1296. The research conducted on Siberut Island, situated in the western part of Sumatra, focuses on traditional communities practicing an agroforestry land management system. This study aimed to identify the plant species within agroforestry land, their respective uses, and techniques for adapting these species to the landscape in two villages, Matotonan in South Siberut District and Bojakan in North Siberut District, Mentawai Islands. Data collection involved direct observation, unstructured interviews for plant species utilization, and transects with a 10m width along contour lines for landscape data. The findings revealed that Siberut's traditional agroforestry land, known as